Structural Therapy With a Couple Battling Pornography Addiction. - Ford, JeffreyJ.; Durtschi, JaredA.; Franklin, DarrellL. (American Journal of Family Therapy)
Pornography increasingly affects couples’ relationships commensurately with the increasing availability of pornographic material. Relationships can be adversely affected by the addictive influences of pornography, and therefore therapists are likely to encounter this concern with their clients. It is suggested that addiction to pornography can be characterized by withdrawal and tolerance, and can have neurological impacts and negatively influence relationships. However, clinicians sometimes fail to recognize pornography addiction to be equally as troublesome as other addictions. This paper explores the implementation of successful structural therapy treatment of pornography addiction using an actual case study with a married couple.